PEMBELAJARAN BERBASIS KOMPUTER MODEL DRILLS TERHADAP KEMAMPUAN BERHITUNG ANAK AUTIS KELAS IV DI SLB - Usfia Lestari, Binari (Jurnal Pendidikan Khusus, 2017)
Abstract: Problem in the cognitive field of autistic children one of them is a mathematical ability that includes counting. This study aims to determine the effect of computer-based learning drills model to the ability to count the fourth-grade autism children in SLBN Pandaan. The developed aspect is the ability of addition and subtraction of 1 to 20. This research uses quantitative research approach with pre-experimental research type and research design one-group pretest-posttest design. Subjects in this study were 6 children with autism. Technique of collecting data that is in the form of test. While the technique of data analysis using non parametik statistic with Wilcoxon test. The results showed that before the treatment/pre-test the average value obtained is 46.7 and after the given treatment/post-test average value obtained by 80. Value Zh = 2.20 is greater than the value of crisis 5 % Zt = +1,96 which means Ho is rejected and Ha accepted, so it can be concluded that computer-based learning drills model have a significant effect on the ability to count autistic class IV in SLBN Pandaan. Keywords:  computer based learning drills model, counting